1983
DOI: 10.1111/j.1365-2273.1983.tb01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in oral squamous carcinoma and their relation to clinical staging

Abstract: One hundred and three patients with an oral squamous carcinoma were studied in an attempt to determine the clinical factors which affect survival. The 5 yr actuarial survival of the whole group of patients was 55%. Although survival depended on clinical staging, in those patients with no palpable nodes on presentation the tumour size did not affect survival. The most significant factor determining survival was the presence of palpable lymph nodes on presentation. Palpable nodes were more likely in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 15 publications
2
15
1
1
Order By: Relevance
“…The presence of lymph node metastases is clinically the most important prognostic factor in oral cavity carcinoma (Hibbert et al, 1983). This is corroborated by the present findings.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of lymph node metastases is clinically the most important prognostic factor in oral cavity carcinoma (Hibbert et al, 1983). This is corroborated by the present findings.…”
Section: Resultssupporting
confidence: 91%
“…The site and size of the primary tumour and the presence of metastases have been used as prognostic indicators (Lee et al, 1972;Krause et al, 1973;Fletcher, 1979). The presence of cervical lymph node metastases seems to be the most important predictor associated with approximately 50 per cent reduction of the 2-year determinate survival rate (Hibbert et al, 1983; Teichgraeber et al, 1973;Willen et al, 1975; Lund et al, 1975) have cavity carcinoma provides useful prognostic information but has certain limitations. The single method treatment of stage I cancer carries a much poorer prognosis than was previously thought, and the incidence of microscopic cervical metastases is high (Lee et al, 1972;Krause et al, 1973;Teichgraeber et al, 1984).…”
mentioning
confidence: 99%
“…The prognostic value of TNM staging of oral malignancy has been called into question by numerous authors [4][5][6][7]. In our study, the cT predicted pT in only 46.2% of cases.…”
Section: Discussioncontrasting
confidence: 45%
“…Criticism of the current TNM (tumour, node, metastasis) staging criteria has resulted from several studies showing that the size-based T criteria fail to demonstrate a significant relationship with patient survival [4,5]. Lenz et al [6] found that clinical T stage (cT) of oral cancer predicted the pathology T stage (pT) only 47% of the time.…”
Section: Introductionmentioning
confidence: 99%
“…3,[31][32][33] . Multivaried analysis shows that D cyclin and neck metastasis are independent factors as to their relation with survival, agreeing with the results from Han et al 13 .…”
Section: Discussionmentioning
confidence: 99%